2007
DOI: 10.1561/1100000004
|View full text |Cite
|
Sign up to set email alerts
|

End-User Privacy in Human-Computer Interaction

Abstract: The purpose of this article is twofold. First, we summarize research on the topic of privacy in Human-Computer Interaction (HCI), outlining current approaches, results, and trends. Practitioners and researchers can draw upon this review when working on topics related to privacy in the context of HCI and CSCW. The second purpose is that of charting future research trends and of pointing out areas of research that are timely but lagging. This work is based on a comprehensive analysis of published academic and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(87 citation statements)
references
References 143 publications
(237 reference statements)
3
81
0
3
Order By: Relevance
“…Iachello and Hong [13] note that "a concept of tradeoff is implicit in most discussions about privacy." For instance, Chawla et al [8] states that "there are two fundamentally conflicting requirements: privacy for the respondents and utility of the sanitized data."…”
Section: A Sweet Spot In Design Where Privacy and Utility Alignmentioning
confidence: 99%
“…Iachello and Hong [13] note that "a concept of tradeoff is implicit in most discussions about privacy." For instance, Chawla et al [8] states that "there are two fundamentally conflicting requirements: privacy for the respondents and utility of the sanitized data."…”
Section: A Sweet Spot In Design Where Privacy and Utility Alignmentioning
confidence: 99%
“…A comprehensive review of literature on privacy evaluation methodologies (e.g. Chiasson et al, 2006;Cranor et al, 2006;DeWitt and Kuljis, 2006;Hawkey and Inkpen, 2007;Iachello and Hong, James et al, 2007) indicated that many times, privacy researchers opt for controlled laboratory studies, especially in the early stages of the work to examine the viability of an approach before proceeding to more fundamental implementation/evaluation schemes. In the absence of an active OpnTag user community and considering that our goal at this stage was also finding out whether our framework yields a viable approach for improving privacy management and to get feedback on its potential problems to refine the design, we also settled for a controlled laboratory study of a small sample.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Recent research in the area of knowledge management (KM), however, has recognised the need to improve people's ability to control who sees what from the information they deposit in their online personal spaces (Erickson, 2006). Nevertheless, the topic of personal privacy-how people manage privacy of their own information with respect to other individuals (as opposed to organisational privacy (Iachello and Hong, 2007)-remains largely unexplored in the research literature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the weakness of most websites and personalization's web, existing operations with the end-user privacy and preferences should be customized. Iachello and Hong (2007) explain that privacy is becoming a critical element of the design of interactive systems in different areas, such as health services, office work, electronic commerce, and personal communications (International Labour Organization, 1993; U. S. Department of Health and Human Services, 2003;Cranor, 2003). …”
Section: Introductionmentioning
confidence: 99%